PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMUNIKASI, DAN DISIPLIN TERHADAP KINERJA PEGAWAI (STUDI PADA KANTOR PDAM KABUPATEN GROBOGAN) - Oktaviana Tri Wulandari, 11.05.51.0101 (Students Journal of Economic and Management, 2015)
This study examines the effect of transformational leadership style, communication, and discipline of the employees performance This research was conducted in the Office of PDAM Â Grobogan. The population was 221 employees and the total sample was 120 employees The sampling method using simple random sampling and the sample size was determined using a formula Slovin. The relationship and or influence between variables is described by the method of multiple regression analysis.The results showed that transformational leadership style, communication, and discipline has positive effect and significant on employee performance. So, if the transformational leadership style, communication, and discipline getting better , it will be better the resulting performance of employees. Keywords: Transformational Leadership Style, Communication, Discipline, and Employee Performance